Marine litter in the Croatian part of the middle Adriatic Sea: Simultaneous assessment of floating and seabed macro and micro litter abundance and composition. (February 2019) - Palatinus, Andreja; Kovač Viršek, Manca; Robič, Uroš; Grego, Mateja; Bajt, Oliver; Šiljić, Jasna; Suaria, Giuseppe; Liubartseva, Svitlana; Coppini, Giovanni; Peterlin, Monika
Abstract: In this study, abundance, distribution and composition of floating and seabed macro and micro litter in the Central Adriatic Sea were assessed. Floating macro litter observations were made. Floating and seabed micro litter were sampled with manta net and Van Veen grab, respectively. Micro litter particles visually found under the microscope were chemically analyzed with Fourier Transform Infrared microscope. Average calculated concentrations of floating macro (175 items/km 2 ), floating micro (127 thousand particles/km 2 ) and seabed micro litter (36 particles/100 g dry weight) show similar values as other published studies from the Mediterranean Sea. A statistically significant ( p  < 0.01) correlation between the floating micro and macro litter concentrations was found for the sites located in the channel waters. Disagreement between model and observations revealed gaps in our knowledge concerning the sea circulation and litter sources. Simultaneous samplings and observations of marine litter in different marine compartments proved possible, efficient and informative. Highlights: First simultaneous data on macro and micro litter at sea (seasurface and seabed). Correlation between floating macro and micro litter was found. No correlation between floating and seabed micro litter was found. Observation vs. model mismatch shows knowledge gaps in circulation and litter sources.